Violent extremism breakthroughs in research and practice (IGI Global, 2019)
"This book is a critical source of academic knowledge on the social, psychological, and political aspects of radicalization and terrorist recruitment. Highlighting a range of pertinent topics such as counterterrorism, propaganda, and online activism"...